APLIKASI INVERS MATRIKS DALAM PEMBENTUKAN PESAN RAHASIA - Side, Syafruddin; Syahrana, Syahrana (Teknosains: Media Informasi Sains dan Teknologi, 2015)
One thing that can be improved its implementation in Linear Algebra is Invers Matrix. Two Matrix is invers if two square matrix have same order, matrix A and B that fulfill the characteristic AB=BA=I, matrix B iscalled multiplication invers from matrix A and it is notated with A-1, just the opposite, matrix A is called multiplication invers from B that is notated with B-1. This research purpose is to know employing invers matrix in making secret message by using matrix adjoin to determine invers from a matrix and employing softwareMicrosoft Visual Basic 6.0 in making message. The steps of employing matrix invers in making secret message are: (1) determining transformation matrix P,(2) secret message is notated in matrix, (3) multiplying matrix P and Q with the result PQ, (4) matrix is changed into text message with modulus operation (5) to know sense of the message, the receiver multiplies P-1and matrix PQ with the result the same initial code. When the initial code is same it means that the sense of the message is known by the receiver. The conclusion of the research are; (1) matrix invers by using matrix adjoin is easier than using other method because mathematics operation in involving simple operations, in despite of carefulness is needed. (2) employing invers matrix in making secret message is more efficient by using softwareMicrosoft Visual Basic 6.0.